Jesuit higher education in a secular age : a response to Charles Taylor and the crisis of fullness - Hendrickson, Daniel Scott (Georgetown University Press, 2022)
In Jesuit Higher Education in a Secular Age, Creighton University President Daniel S. Hendrickson, SJ, shows how contemporary Jesuit education can foster greater self-awareness, a stronger sense of global solidarity, and an aptitude for inspiration, awe, and gratitude among their students.